Occult child abuse presenting as pneumatosis intestinalis and portomesenteric venous gas - a case report - En-Pei Lee; Jainn-Jim Lin; Shao-Hsuan Hsia; Oi-Wa Chan; Han-Ping Wu (BMC, 2019)
Abstract Background Pneumatosis intestinalis and portomesenteric venous gas are usually caused by necrotizing enterocolitis; however they can occur secondary to abusive abdominal trauma with bone fractures and bruising. It is difficult to recognize initially if there is no bruising on the skin or bone fractures. Case presentation We report a 1-year-old child with no obvious history of trauma who presented with conscious disturbance. Abdominal computed tomography showed acute ischemic bowel complicated with pneumatosis intestinalis and portomesenteric venous gas. The first impression was septic shock with acute ischemic bowel. Two weeks after admission, brain magnetic resonance imaging showed subdural hemorrhage of different stages over bilateral fronto-parietal convexities and diffuse axonal injury, suggesting abusive head trauma. He was subsequently diagnosed with occult child abuse. Conclusion Pneumatosis intestinalis and portomesenteric venous gas are rare except in cases of prematurity. Occult abusive abdominal trauma should be considered as a differential diagnosis in patients with pneumatosis intestinalis and portomesenteric venous gas, even without any trauma on the skin or bone fractures.